Using Language to Rage against Victorian Hierarchy: Self-constructed Feminist Identity in Jane Eyre - Yao Chiachen; Ya-huei Wang (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
All human beings seek certain identities in order to understand their existence and position in society, the groups to which they belong, and the unique characteristics they have. This paper examines how, in Jane Eyre, Charlotte Bronte examines socially constructed institutionalism in Victorian England. This paper also explores how the protagonist, Jane Eyre, oppressed due to her social class and gender, struggles to live with equality, dignity, and freedom, and finally reaches independence and self-fulfillment. Jane successfully completes the stages of identity development, and, after acquiring a sense of competence, achieves happiness and intimacy in an equal partnership with her true love, Mr. Rochester.